Communication Channel Reconstruction for Transmission Line Differential Protection: System Arrangement and Routing Protocol - Xu Chen; Xianggen Yin; Bin Yu; Zhe Zhang (Energies, 2016)
Natural disasters may be of significant impact on overhead transmission lines and cause communication outage related to pilot protection. This paper aims at reconstructing communication channels and maintaining functions of pilot-wire differential protections after the main channel fails. With the development of smart grids as well as new communication technologies, wireless sensor networks (WSNs) have been potential means for realizing reconstructed communication channels (RCCs) without further installation. For a reliable design, system arrangement and the communication structure were presented. Theoretical planning of sensor nodes was formulated, which enjoys advantages such as high reliability, cost optimization, and capacity of satisfying the connectivity of the communication network. To meet the need of time delay, a novel routing protocol for WSNs was proposed with three stages including route establishment, route discovery and route maintenance, which ensured the directional propagation of data packets. Practical experiments and simulation results indicate that the proposed RCC scheme can satisfy time delay of protection relaying in emergency communication channel, as well as guarantee the connectivity of networks when some WSN nodes are damaged.